The Role Real Estate Tax Avoidance in Indonesia - Arisanjaya Doloan; Nuratni Botutihe (Proceeding of The International Conference on Business and Economics, 2023)
Finding dependent variables that affect tax evasion is the goal of this study. The three variables that are calculated independently are leverage, profitability, and business size. Secondary data for the years 2021–2023 that is gathered annually from the Indonesian Stock Exchange is used in this study. The purposive sampling strategy was applied for four years, from 2021 to 2023, to gather 84 samples from 26 companies. This research was processed using the Eviews 10 application. Multipliers such as Chow, Lagrange, and Hausman are employed. The employment of leverage affects tax evasion. Profits and company size, however, have no bearing on tax evasion